Penggelapan Barang Tidak Bergerak dan Penyerobotan Hak Atas Tanah (Studi Kasus Putusan Nomor 15/Pid.B/2020/Pn Mlg) - Darma Syah Putra (LAW Proscientist: Journal of Law Profesional Scientist, 2022)
Land grabbing is not something new and is happening in Indonesia. The word expropriation itself can be interpreted as an act of taking rights or assets arbitrarily or by ignoring laws and regulations, such as occupying other people's land or houses, which are not their rights. Unlawful land grabbing is an act against the law, which can be classified as a criminal act. In writing this research, the authors raised two problems, namely: 1). Is the crime of land grabbing in the Case Decision Number 15/Pid.B/2020/PN Mlg including the crime of embezzlement of immovable property?; and 2). What is the criminal responsibility for land grabbing in the Decision on Case Number 15/Pid.B/2020/PN Mlg? This research method is a method used to obtain data and obtain accurate answers to the formulation of the problem above by searching and managing data in a study. This type of research is normative legal research. The author uses three methods of approach including a conceptual approach (conceptual approach), statutory approach (statute approach), and case approach (case approach). The title of the research being proposed is: Crime of Land Seizure and Embezzlement of Immovable Property (Case Study of Decision Number 15/Pid.B/2020/Pn Mlg).